Sistema de wetlands construídas associados ao contexto urbanístico e paisagístico: estudo de caso de Barra Bonita/SP - Mariano, Maximiliam Borges (Universidade Federal de São Carlos, 2017)
The similarity of the wetlands system with natural landscape, scenic beauty confirmed, attributes to it a unique characteristic, which allows the usage of the surrounding area for leisure activities, sports practice, environmental education, tourism, among others. This paper aims to evaluate the potential benefits and the challenges of implanting a wetlands system consorted to an urban park, as post-treatment of effluent treated in a lagoon system, in a sugar-ethanol sector company located in Barra Bonita, Brazil, SP. The methodology used is based on the information gathering and compilation in bibliography and primary data collected through the collection and laboratory analysis. The final product presented the real and necessary dimensions for the implementation of a wetlands system associated to an urban park and indicated the best location for the implementation of the project considering the physical, urban and legal aspects, through the association of the proposed areas with the guidelines of the Integrated Master Plan of the municipality, but also demonstrated that connecting a wetlands treatment system to an urban park can be an effective alternative to develop social, environmental and urban aspects to the municipality and its population
Keywords: Parque urbano; Sucroenergético; Barra Bonita; Wetlands; Urban park; Sugar-ethanol company; CIENCIAS SOCIAIS APLICADAS::ARQUITETURA E URBANISMO::PAISAGISMO; ENGENHARIAS::ENGENHARIA SANITARIA; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL::QUALIDADE DO AR, DAS AGUAS E DO SOLO